Peran Keluarga Kawin Campur dalam Pendidikan Iman Anak di Quasi Paroki St. Markus-Waikambala - Njuma, Hendrikus Kota (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2025)
The purpose of this study was to determine the extent to which parents of mixed marriages play a role in educating their children's faith and what methods or forms are applied by mixed marriage families in educating their children's faith. The method used in this study was qualitative with data collection techniques through interviews and documentation. To obtain more valid and in-depth data, the researcher used the in-depth interview method. From the findings during the study, all interfaith parents who were the targets of this study were very concerned about the faith education of their children. This finding certainly slightly refutes the assumption that there is an apathetic attitude of interfaith parents towards the faith needs of their children. The conclusion is that the Church must continue to maintain and continue to monitor the continuity of children's faith education in interfaith families. The results of this study certainly do not automatically eliminate the negative stigma related to the deviation of children's faith in interfaith families. The Church must remain with them so that interfaith parents remain committed to educating their children in faith.